Organizational Excellence in Palestinian Universities of Gaza Strip - Amal A. Al hilaa; Mazen J. Al Shobakib; Youssef M. Abu Amuna; Samy S. Abu Naser (International Journal of Information Technology and Electrical Engineering, 2017)
The research aims to identify the organizational excellence in Palestinian universities of Gaza Strip, from the perspective of senior management. The questionnaires were distributed the top senior management in the Palestinian universities, and the study population was (344) employees in senior management in Palestinian universities. A stratified random sample were selected from of employees in the Palestinian universities consist of (182) employees at return rate of (69.2%). SPSS program for analyzing and processing the data was used. The study reached the following results: the senior management agrees largely on the importance of the axis of "Leadership Excellence" and "Excellence service sectors". The senior management agrees moderately about the importance of the axis of the “Knowledge excellence". The study showed that there is a weakness in the employment of scientific research to serve the community, there is weakness in the follow-up of the universities management for the performance of their graduates in the institutions in which they work. Senior management agrees on the importance of the "Organizational Excellence" moderately. The recommendations of study includes: the need to develop principles and fair criteria for the selection of the best candidates for the university and university leaders based on specialization, competence, experience, skills, integrity and not on the basis of favoritism.
Keywords: 330; Organizational Excellence; Leadership Excellence; Senior Management; Palestinian universities; Gaza Strip